Hubungan Lemak Tubuh dengan Kesehatan Selama Menstruasi pada Remaja di MTs Islamic Kedawung - Erida Erida; Sumarmi Sumarmi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Adolescent in the world in 2024 amounted to 1.9 billion girls of reproductive age experiencing menstruation, in Indonesia as many as 70.1% of adolescents have experienced menstruation, in West Java as many as 72.5% of adolescents have experienced menstruation and in Cirebon Regency as many as 73.3% have menstruating. The purpose of this study was to determine the relationship between body fat and health during menstruation in adolescents at MTs Islamic Kedawung.This research method uses correlational descriptive with cross sectional approach. The sample of this study was female students who were menstruating, totaling 60 respondents, the sampling technique was accidental sampling. The instrument used is body fat, namely skinfold and menstrual cycle related signs and symptoms (MCSs) questionnaires, as well as data analysis using the spearman rank test. This research was conducted on young women at MTs Islamic Kedawung on 29 June 2022 – 7 Juny 2022.The results showed that body fat in adolescents was (56.7%) in the ideal category and health during menstruation in adolescents was (63.3%) in the no severity category. The results of the bivariate analysis using the Spearmank rank test showed p value < and r < 1.00 with a positive correlation direction, meaning that H0 was rejected, so there was a significant positive and strong correlation between body fat and health during menstruation in adolescents at MTs Islamic Kedawung, which means the more ideal body fat, the health during menstruation is getting less severe (p value= 0.000; = 0.05; r= 0.615).Adolescent are strived to be able to maintain a balance of body fat and health by routinely carrying out activities and adequate nutrition for health during menstruation.